Greening the supply chain towards sustainability : a holistic approach for mitigating industrial environmental impacts with sustainable improvements on firms’ environmental, economic, and social performances in the automotive industry - Abari, Saheed (2020)
This study is aimed at examining the process of greening the supply chain as a holistic and pragmatic approach for mitigating industrial environmental impacts in the automotive industry. The research addresses the fundamental requirements, and also attempt to unbundle the complications and barriers firms encounter in the process of greening their supply chains in addition to providing a clear path to sustainability by devising a workable framework, and practical steps that will guide firms to achieving a green and sustainable supply chains.